2015
DOI: 10.1111/mmi.13254
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy reveals a dual collagen‐binding activity for the staphylococcal surface protein SdrF

Abstract: SummaryStaphylococcus epidermidis causes nosocomial infections by colonizing and forming biofilms on indwelling medical devices. This process involves specific interactions between cell wall-anchored (CWA) proteins and host proteins adsorbed onto the biomaterial. Here, we have explored the molecular forces by which the S. epidermidis CWA protein serine-aspartate repeat protein F (SdrF) binds to type I collagen, by means of advanced atomic force microscopy (AFM) techniques. Using single-cell force spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
3
16
0
1
Order By: Relevance
“…6C). Herman-Bausier and Dufrêne had previously demonstrated two distinct binding events/peaks, a weak and a strong peak, are typically observed in ColBD and collagen interactions [30]. In the current study, a weak signature peak of 36 pN and a stronger signature peak of 91 pN were observed in the interaction of Res-ColBD with collagen I (Fig.…”
Section: Resultssupporting
confidence: 70%
“…6C). Herman-Bausier and Dufrêne had previously demonstrated two distinct binding events/peaks, a weak and a strong peak, are typically observed in ColBD and collagen interactions [30]. In the current study, a weak signature peak of 36 pN and a stronger signature peak of 91 pN were observed in the interaction of Res-ColBD with collagen I (Fig.…”
Section: Resultssupporting
confidence: 70%
“…These forces of interaction between aggrecan and the hydrogel slightly increase from 0.97 to 1.25 nN with increasing DS of gel-MA. The forces detected are in the same range compared to the forces detected between proteins and biomaterial surfaces including collagen and hyaluronic acid (Donlon, Nordin, & Frankel, 2012;Herman-Bausier & Dufrene, 2016). …”
mentioning
confidence: 78%
“…SdrG thus appears to be a formidable player in staphylococcal adhesion to Fg-coated medical implants. Examples also exist of Sdr proteins that interact with other extracellular matrix proteins, such as S. epidermidis SdrF that is responsible for its binding to Cn, which involved weak as well as strong bonds (Herman-Bausier and Dufrêne, 2016).…”
Section: Serine-aspartate Repeat Proteins and Clumping Factorsmentioning
confidence: 99%